MORAL VALUES AND CULTURAL IDENTITY IN INDONESIANCHILDREN’S SONG LYRICS: A DISCOURSE ANALYSIS: A Discourse Analysis - Eka Nur Ramadhani; Gisca Tri Maura Kunti; Sofi Sofi Nurazizah; Suci Chalista; Yovanka Digna Margareta; Siamir Marulafau; Erikson Saragih (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This writing entitled